Censurae Librorum - Usakiewicz, Joanna (Polskie Towarzystwo Filologiczne, 2018)
Rosie Wyles, Edith Hall (eds.), Women Classical Scholars. Unsealing the Fountain from the Renaissance to Jacqueline de Romilly, Oxford: Oxford University Press, 2016, XVIII + 465 pp., ISBN 978-0-19-872520-6, £80.00.
Keywords: censurae librorum